Total Quality Management and Its Impact on The Effectiveness of the Academic System in Higher Education - Muhith, Abd; Mislikhah, St.; Fatmawati, Erma; Umam, Khotibul; Mu'allimin, Mu'allimin (JURNAL AL-TANZIM, 2022)
This paper describes total quality management and its impact on the effectiveness of the academic system at KH Achmad Siddiq State Islamic University Jember. This research uses a qualitative case study approach, using interviews, observation, and documentation as data collection techniques. Participants in it are leaders, lecturers, staff, and students with the purposive sampling technique. The data analysis uses Milles and Huberman's concepts, namely data reduction, data presentation, and conclusions. The results showed that the impact of total quality management and the effectiveness of the academic system was; 1) Using friendly, namely students and lecturers as users in this research, it becomes easier to use technology-based information systems, not complicated in using and getting services regarding academic matters; 2) Ease of access to information, namely making it easier for students to access information about academics; 3) Faster use, due to managerial processes that get more attention, students and lecturers feel faster in digging up information through accounts that have been provided with accurate results; 4) Public services faster, managerial processes that run more effectively and consistently as well as the presence of experts who manage them make students feel satisfied with college academic services.